JAK inhibitors to treat STAT3 gain-of-function: a single-center report and literature review - Atschekzei, Faranaz; Traidl, Stephan; Carlens, Julia; Schütz, Katharina; von Hardenberg, Sandra; Elsayed, Abdulwahab; Ernst, Diana; Risser, Linus; Thiele, Thea; Graalmann, Theresa; Raab, Juliana; Baumann, Ulrich; et al. (Frontiers in Immunology, 2024)
The signal transducer and activator of transcription 3 (STAT3) gain-of-function (GOF) syndrome (STAT3-GOF) is an inborn error of immunity (IEI) characterized by diverse manifestations immune dysregulation, that necessitate systemic immunomodulatory treatment. The blockade of the interleukin-6 receptor and/or the inhibition of the Janus kinases have been commonly employed to treat diverse STAT3-GOF-associated manifestations. However, evidence on long-term treatment outcome, especially in case of adult patients is scarce.Methods: Clinical data, including laboratory findings and medical imaging, were collected from all 7 patients, diagnosed with STAT3-GOF, that have been treated in the Hannover University School, focusing on those that received a Janus kinase (JAK) inhibitor (JAKi). Previously published cases of STAT3-GOF patients, who received a JAKi were evaluated, focusing on reported treatment efficacy with respect to diverse STAT3-GOF-associated manifestations of immune dysregulation and safety.Results: Five out of 7 patients diagnosed with STAT3-GOF were treated with a JAKi, each for a different indication. Including these patients, outcomes of JAKi treatment have been reported for a total of 41 patients.Treatment with a JAKi led to improvement of diverse autoimmune, inflammatory or lymphoproliferative manifestations of STAT3-GOF and a therapeutic benefit could be documented for all except two patients.Considering all reported manifestations of immune dysregulation in each patients, complete remission was achieved in 10/41 (24.4%) of treated patients.JAKi treatment improved diverse manifestations of immune dysregulation in the majority of STAT3-GOF patients, representing a promising therapeutic approach. Long-term follow-up data are needed to evaluate possible risks of prolonged treatment with a JAKi.